PENGARUH MOTIVASI KERJA TERHADAP KINERJA DOSEN STIE TOTALWIN SEMARANG - HAKIM, LUKMANUL (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2011)
Organization as a system of behavior included input, process and output. A collection of people, facilities and infrastructure could be used as input for further processing. Form and the process can be the interaction of people involved in the organization. The form of output was a result of cooperation in implementing something to achieved the same goal. The general purpose of operation can not function when not translated into specific objectives. Its not easy to measure achievement objectives for organizations that do not produce tangible outputs such as in the College of Economics Totalwin Semarang engaged in the business of education services. In such organizations, faculty and staff input is a factor that perform a process in order to create good output. One of the problems still faced by the existing College of Economics Totalwin Semarang until now was "Why do some lecturers work better than other lecturer?" One of the tasks Management College of Economics Totalwin Semarang was to identify the causes of things that could happen. Source of effectiveness of lecturers include motivation, ability, knowledge, skills, attitudes and stress. The differences are influenced by the motivation of work and that can lead to different performance of each faculty. The problem in this study were 1). Work motivation could affect on the performance of lecturers STIE Totalwin Semarang. 2). Which was the factor of work motivation could dominant affected the lecturer performance in STIEÂ  Totalwin Semarang The sample in this study was 31 lecturer in STIE Totalwin Semarang. Analysis tools used test validity and reliability, multiple correlation analysis and multiple linear regression. The results of this analysis showed r 0.3440 table from 4:12 to 9 points table (variable) has a positive value and valid